The Impact of Sleep Quality on Academic Performance Among Second-Year Medical Students at Al Zawia University - Nawal Hasan; Hwisa, Karima (AlQalam Journal of Medical and Applied Sciences, 2025)
Sleep deprivation is a common problem among medical students, owing primarily to the intense academic schedules and extended study hours that come with medical school. This study examines the impact of sleep deprivation on academic performance among medical students at Al-Zawia University. A study of 230 students (44 males and 186 females) in their second medical year used the Pittsburgh Sleep Quality Index (PSQI) to assess sleep quality and patterns, as well as self-reported academic performance. The research found a negative association between sleep duration and academic performance. Students who had a PSQI score > 10 (indicating poor sleep) performed worse. In addition, sleep patterns varied among genders throughout the same academic year. These findings highlight the need to raise awareness among medical students about the need for appropriate sleep for academic success, mental health, and physical well-being.